2010
DOI: 10.1007/s11306-010-0267-y
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in tumor cell energetic metabolome at different cell cycle phases of human colon cancer cell lines

Abstract: In this present study, the efficacy of metabolomics as a tool for tumor cell energetics for in vitro cell cultures was demonstrated with full competence for the first time by elucidating the anabolic and energy-yielding segments of glycolysis and glutaminolysis, which constitute a part of energy metabolism in tumor cells. By synchronizing colon cancer cells SW480 and SW620 in culture, the metabolome specific to cell cycle phases was analyzed using nuclear magnetic resonance spectroscopy. At the G 1 /S transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…Previous studies of xenographs of HT29, HCT116, and SW620 cells showed that the most common metabolites were amino acids and lactate, indicating that the 1,725 cm −1 peak associated with ν C=O and the 885 and 898 cm −1 peaks probably have a strong contribution from lactate. These peaks show the trend HCT116 > SW620 > HT29 > SW480 ≈ HL60, which also agrees with previous magnetic resonance spectroscopy results . This can be attributed to the Warburg effect, due to which highly proliferative cancerous cells have increased lactate contents; HCT116, SW620, and HT29 are known to have lower doubling times than SW480 and HL60 cells .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Previous studies of xenographs of HT29, HCT116, and SW620 cells showed that the most common metabolites were amino acids and lactate, indicating that the 1,725 cm −1 peak associated with ν C=O and the 885 and 898 cm −1 peaks probably have a strong contribution from lactate. These peaks show the trend HCT116 > SW620 > HT29 > SW480 ≈ HL60, which also agrees with previous magnetic resonance spectroscopy results . This can be attributed to the Warburg effect, due to which highly proliferative cancerous cells have increased lactate contents; HCT116, SW620, and HT29 are known to have lower doubling times than SW480 and HL60 cells .…”
Section: Resultssupporting
confidence: 90%
“…These peaks show the trend HCT116 > SW620 > HT29 > SW480 ≈ HL60, which also agrees with previous magnetic resonance spectroscopy results. [53,61] This can be attributed to the Warburg effect, due to which highly proliferative cancerous cells have increased lactate contents; HCT116, SW620, and HT29 are known to have lower doubling times than SW480 and HL60 cells. [51,[62][63][64] For the carcinoma cell lines, the lactate contribution appears to be correlated with the cancer stage.…”
Section: Average and Multivariate Analysis Of Results Of Multiple Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The region-specific characteristic ions could be attributed to the different metabolite profiles in the heterogeneous regions of the tumor resulting from different cellular activities and/or microenvironment. [22][23][24] The ion profiles of the different regions of the tumor tissue section are provided in Supplementary Fig. S5 (see Supporting Information).…”
Section: Molecular Imaging Of Tumor Tissue and Region Differentiationmentioning
confidence: 99%
“…Cancer cell lines are widely used to study potential therapeutic drugs, to identify proteins with altered expression levels, gene mutations, and inactivation or activation of metabolic pathways [ 12 14 ]. Several metabonomics studies have shown differences in metabolic profiles among different cancer cell lines [ 15 ] and the metabolic processes that occur during apoptosis and cell cycle phases [ 16 , 17 ]. In addition, monitoring metabolic profiles can also be useful to study the effect of various stimuli such as drug treatments [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%